Dampak Program Pembangkit Listrik 35.000 MW terhadap Tingkat Pekerjaan dan Kemiskinan di Indonesia - Anggoro, Yohanes Dwi; Rezki, Jahen Fachrul (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
This research analyzes the 35,000 MW Program’s impact on employment and poverty levels in Indonesia using the Callaway and Sant’Anna Difference-in-Differences (CSDID) method. The research uses panel data at the district/city level from 2007 to 2022. The analysis shows the program has a significant impact on reducing poverty, with an average reduction of 5,208 poor people in Model 1; 4,277 people in Model 2; and 4,284 people in Model 3. Based on a subset of regions, the analysis shows the program had a significant impact on increasing the employment rate by 1.2 percent, reducing 16,034 poor people in the Java-Madura-Bali.